TECHNICAL EFFICIENCY ANALYSIS OF SUGAR CANE FARMING IN EAST JAVA, INDONESIA (Statistical Approach of Frontier Production Functions) - Ika Purnamasari; Nuhfil Hanani, AR; Suhartini Suhartini (Agricultural Socio-Economics Journal, 2018)
These research goals are to analyze the factors that affect the production of sugar cane, to analyze the level of technical efficiency of farming sugar cane, and to analyze the factors that technical inefficiency affecting sugar cane farming in the dry land and irrigated land. Methods of data analysis that is used to find out the factors that affect the production of sugar cane and the level of technical efficiency of sugar cane farming is a stochastic production frontier. In order to find the factors that affect technical inefficiency of sugar cane efficiency, Tobit analysis is applied. The results show that the influential factors towards the production of sugar cane in the dry land i.e. number of seedlings and the number of labor, while sugar cane production in the irrigated land are the amount of labor, Urea fertilizer, Ponska fertilizer and herbicides. The average technical efficiency of sugar cane farming achieved in the dry land is 0.887 and the average technical efficiency of irrigated land is 0.928. Factors that influence technical inefficiency of sugar cane farming in the dry land are rejuvenation of sugar cane (keprasan), frequency of counseling, and seeds. While the factors for irrigated land are rejuvenation of sugar cane (keprasan) and frequency of counseling.